Assessment of Edu-Communication Strategies in Agricultural Extension Services Delivery on Adoption of Improved Sesame Production Practices in Niger State, Nigeria - Ibrahim, M (Journal of Agricultural Extension Management, 2024)
The study examined edu-communication strategies used by agricultural extension service agencies in the dissemination of improved sesame production practice among sesame farmers in Niger State Nigeria. Two hundred and Eighty (280) sesame farmers were sampled and structured questionnaires along with discussion guide were used to elicit primary data from respondents. The Primary data were collected and analysed with SPSS 16.0. The results showed that, mean age was 35years. The majority (61.4%) were male, and 85.7% were married. Additionally 71.4% had no formal education. Audio-visual aids and face-to-face contact ranked 1st and 2nd among edu-communication strategies deployed by extension agents. Traditional town criers (¯x=3.9) and market square announcements ranked 1st and 2nd as a major indigenous tools used in disseminating improved sesame production practices. The Innovative edu communication strategy exposes sesame farmers to the types of chemicals to use in their farms ranked 1st and the quantity of seed used by sesame farmers to cultivate a hectare of farm land was made known by AEOs ranked second in terms of Respondents’ perception on the role of edu-communication strategies on adoption. Majority (71%) of the respondents view farmer’s field visits by AEOs as the most important medium that have effects on the adoption behaviour among sesame farmers. Low educational status (x=3.36) ranked first indicating that their low educational backgrounds significantly impedes their understanding and subsequent adoption decision. It was recommended that western education in addition to indigenous knowledge should be pay more emphasis to broaden their knowledge of agriculture extension services approaches for the high rate of adoption.